Etiology of Hepatocellular Carcinoma in Italian Patients with and without Cirrhosis - CHIESA, R; DONATO, F; BONETTI, M; BETTINI, L; PELIZZARI, G; SALMI, A; SAVIO, A; GARATTI, M; CALLEA, F; TAGGER, A; FAVRET, M; RIBERO, M. L; et al. (Cancer epidemiology, biomarkers & prevention, 2000)
We performed a case-control study to assess the role of hepatitis B virus (HBV), hepatitis C virus (HCV), GB virus C/hepatitis G virus (HGV), TT virus, alcohol intake, and tobacco smoking as risk factors for hepatocellular carcinoma (HCC) in the presence or absence of cirrhosis. We prospectively recruited 174 patients with a first diagnosis of HCC admitted to the main hospitals in Brescia, North Italy. On the basis of histological, clinical, and radiological criteria, the presence of cirrhosis was established in 142 cases, excluded in 21 cases, and remained undefined in 11 cases. Among the HCC cases without cirrhosis, a histological picture of normal liver was found in a single patient, chronic viral hepatitis was found in 11 patients, alcoholic hepatitis was found in 5 patients, nonspecific reactive hepatitis was found in 3 patients, and hemochromatosis was found in 1 patient. As controls, we also included 610 subjects unaffected by hepatic diseases and admitted to the same hospitals as cases. The odds ratios for having HCC according to positivity for HCV RNA, HBsAg and/or HBV DNA, and alcohol intake > 80 g/day (95% confidence interval) were as follows, in the presence and absence of cirrhosis, respectively: ( a ) 33.5 (17.7–63.4) and 19.7 (6–64.8) for HCV RNA; ( b ) 17.6 (9.0–34.4) and 20.3 (5.7–72.6) for HBsAg; and ( c ) 5.5 (3.1–9.7) and 4.6 (1.5–13.8) for alcohol intake. No association was found with HGV or TT virus infections or tobacco. This study has shown that most HCC cases arising in the area are due to HBV, HCV, or alcohol intake, in both the presence and absence of cirrhosis.